MORAL AND GENDER IDENTITY IN THE STORY OF THE BUTTERFLY IN THE MOSQUE - Rhani Febria; Liliana Muliastuti; Yumna Rasyid (Getsempena English Education Journal, 2022)
Researchers studied this study using Norman Faiclough's theory of critical discourse analysis. Through this theory, the researcher can carry out critical reflections to dismantle the interests of the analyzer. This study describes how moral identity and gender identity are in short stories on republika online media. The approach used is qualitative to understand phenomena about what the subject of the study experiences for example behavior, perception, motivation, action. The data collection technique is carried out by downloading short stories through the Republika e-paper, then describing, analyzing, and interpreting based on critical discourse analysis techniques. The findings of this study are: there are issues of moral and gender identity that are represented by examining the linguistic level and practice of discourse. Based on the findings, it can be concluded that the study of moral and gender identity can dismantle ideologies and aspects hidden in short story texts by looking at linguistic elements through modalities and metaphors; in the practical dimension of discourse shows that short stories contain elements of moral identity and gender identity in line with the vision and mission of the Republika online media that uphold human and cultural values; Factors that influence the development of moral identity and gender include internal factors, namely factors that exist within the character himself, and external factors, namely factors that exist outside the character (environment, lifestyle, friendships).